Does the invasive plague skink (Lampropholis delicata) compete with native skink species in New Zealand?. (15th December 2020) - Harris, Jaclyn; Smith, Chelsea R.; van Winkel, Dylan; Brunton, Dianne H.; Goulet, Celine T.; Chapple, David G.
Abstract: Invasive species are a major threat to biodiversity worldwide, causing many of the recent declines and extinctions of native species. Competition is a common mechanism through which invasive species impact the native biota. In particular, exploitative competition results when the invader outcompetes native species for essential resources, such as food and shelter sites. Despite being pervasive invaders, the ecological impacts of invasive lizards are understudied and it is often unknown whether these invaders have detrimental impacts. The plague skink ( Lampropholis delicata ), native to eastern Australia, has invaded several locations throughout the Pacific region (Hawaiian Islands, New Zealand, Lord Howe Island). However, no studies have documented the plague skink as having a negative impact on native species anywhere throughout its introduced range. Here, we conducted a mark‐recapture study in northern New Zealand (Shakespear Regional Park) to investigate whether the plague skink competes with native skink species ( Oligosoma aeneum, O. ornatum, O. moco ). Though the plague skink has a broader distribution within the study region and occurred across a broader range of habitats, there was substantial range and niche overlap between the plague skink and the three native skink species. Both the absolute capture rates and estimated population size of the plague skink were significantly higher than the three native skink species. Although plague skinks have smaller body sizes well as shorter and narrower heads than the native skink species, there was still considerable scope for dietary overlap among the species. While our study does not provide definitive evidence for competition between the plague skink and native skink species in New Zealand, we clearly demonstrate the presence of the core components required for exploitative competition to occur. Further field‐ and laboratory‐based studies will be required to confirm the existence of exploitative or interference competition by the plague skink in its introduced range.